The Effect of Health Education on Family Knowledge in Caring for Patients with Hypertension - Puspitadewi, Icha; Hadiyanto, Hendri; Abdillah, Hadi; Hamidah, Ernawati (Jurnal Keperawatan Priority, 2025)
Hypertension is a major health problem that requires effective management not only by the patient but also through the support and knowledge of the family. This study aims to determine the effect of health education on family knowledge in caring for patients with hypertension in the working area of Surade Public Health Center. This research used a pre-experimental design with a one-group pretest-posttest approach. The population in this study consisted of 71 family members of hypertensive patients, selected using a total sampling technique. Data collection was carried out using a knowledge questionnaire administered before and after the health education intervention, which was conducted in a 45-minute session using verbal explanations, visual materials, and interactive discussions delivered by trained health educators. The results showed a substantial improvement in the level of family knowledge after the health education intervention. Before receiving education, the majority of respondents (88.7%) were categorized as having poor knowledge, with only 5.6% each in the good and fair categories. After the intervention, there was a significant shift: 28.2% of respondents were categorized as having good knowledge, 69% as fair, and only 2.8% remained in the poor category. These findings indicate that the health education intervention effectively improved the knowledge level of families in caring for patients with hypertension. The Wilcoxon signed-rank test further confirmed this improvement with a significance value of 0.001 (p < 0.05), indicating a statistically significant difference in knowledge levels before and after the intervention. The study concludes that health education has a significant effect on increasing family knowledge in caring for patients with hypertension. Therefore, providing regular and structured health education is highly recommended to empower families in managing hypertension effectively.